Empowerment and Efficiency: Tenancy Reform in West Bengal - Banerjee, Abhijit V.; Gertler, Paul J.; Ghatak, Maitreesh (Journal of Political Economy, 2002)
The paper analyzes the effect of agricultural tenancy laws offering security of tenure to tenants and regulating the share of output that is paid as rent on farm productivity. Theoretically, the net impact of tenancy reform is shown to be a combination of two effects: a bargaining power effect and a security of tenure effect. Analysis of evidence on how contracts and productivity changed after a tenancy reform program was implemented in the Indian state of West Bengal in the late 1970s suggests that tenancy reform had a positive effect on agricultural productivity there.